Alcohol Use, Partner Violence, and Depression: A Cluster Randomized Controlled Trial Among Urban South African Mothers Over 3 Years - Rotheram-Borus, Mary Jane (Am J Prev Med, 2015)
INTRODUCTION: Pregnant South African women with histories of drinking alcohol, abuse by violent partners, depression, and living with HIV are likely to have their post-birth trajectories over 36 months significantly influenced by these risks. DESIGN: All pregnant women in 24 Cape Town neighborhoods were recruited into a cluster RCT by neighborhood to either: (1) a standard care condition (n=12 neighborhoods, n=594 mothers); or (2) a home-visiting intervention condition (n=12 neighborhoods, n=644 mothers). SETTING/PARTICIPANTS: Pregnant women residing in urban, low-income neighborhoods in Cape Town, South Africa. INTERVENTION: Home visiting included prenatal and postnatal visits by community health workers (Mentor Mothers) focusing on general maternal and child health, HIV/tuberculosis, alcohol use, and nutrition. MAIN OUTCOME MEASURES: Mothers were assessed in pregnancy and at 18 and 36 months post birth: 80.6% of mothers completed all assessments between 2009 and 2014 and were included in these analyses performed in 2014. Longitudinal structural equation modeling examined alcohol use, partner violence, and depression at the baseline and 18-month interviews as predictors of maternal outcomes at 36 months post birth. RESULTS: Relative to standard care, intervention mothers were significantly less likely to report depressive symptoms and more positive quality of life at 36 months. Alcohol use was significantly related to use over time, but was also related to depression and HIV status at each assessment and partner violence at 36 months. CONCLUSIONS: Alcohol, partner violence, and depression are significantly related over time. A home-visiting intervention improved the emotional health of low-income mothers even when depression was not initially targeted.